Airway hyperresponsiveness and airway inflammation in elite swimmers - Pedersen, L. (Clinical Respiratory Journal, 2009)
The prevalence of respiratory symptoms and airway hyperresponsiveness (AHR) is high in elite athletes; swimmers have one of the highest prevalences. No consensus exists on what airway challenge to use when identifying AHR in elite athletes. Further, knowledge is sparse about when during their active sport career AHR develops and if there is an acute effect on the airway inflammation of a swimming training session.